MAKING THE CASE FOR HUMAN LIFE EXTENSION: PERSONAL ARGUMENTS - Schloendorn, John (Bioethics, 2006)
In the close to medium future, the life sciences might permit a vast extension of the human life span. I will argue that this is a very desirable development for the individual person. The question whether death is a harm to the dying is irrelevant here. All it takes is that being alive is good for the living person and not being alive is not good for anyone. Thus, living persons who expect to live on happily are rationally required to want to stay alive. Eventual uncertainty whether it will be possible to be happy in the future provides no objection, but rather an incentive to try. This view, however, may be naive in assuming that persons are unchanging entities that exist separately from their psychological information. Objections have been derived from reductionistic views that value our future experiences in a way that declines with time, so that there will be a future point beyond which only negligible value accrues. If we adopt such a view, then we cannot now be concerned to have experiences beyond that point. I argue that these arguments fail to take into account all the reasons we might have to be concerned for the future and all the kinds of such concern that come from them. The adoption of a plausible reductionistic account can arguably weaken our concern for the future and certainly change its quality in important ways. But this provides no objection to the desire to live forever, nor to live at all.